Relationship Between Mental Health and Death Anxiety During COVID-19 Pandemic in Dental Staff and Students: A Cross-Sectional Study - Jazaiery, Mahta; Rezaeifar, Kosar; Sayyah, Mehdi; Cheraghi, Maria (Frontiers in Psychiatry, 2022)
Objective: We aimed to determine the mental health and death anxiety among dental staff and students in school of dentistry during COVID-19 pandemic. Methods It was a cross-sectional study among students (n = 300) and staff (n = 60) in School of dentistry in Ahvaz University of Medical Sciences during 2020. The instruments were a demographic questionnaire, Death Anxiety Scale, and Kessler Questionnaire. Data was analyze by using SPSS version 22, in all tests, the significance level was set at <0.05. Results The mean age of dental students and personnel was 23.96 and 40.08 years, respectively. The mean scores of death anxiety were higher in dental staff (8.53) than students (6.02) and the mean scores of mental health status were higher in students (14.78) than personnel (9.18). This indicates that death anxiety was higher in Dental staff, while students were in better mental health status. The correlation coefficient between death anxiety and mental health status was 0.366 among students (p < 0.001), while it was 0.429 among dental staff (p < 0.001), showing a medium relationship between death anxiety and mental health in both groups. Conclusion The overall findings represent a significant but contradictory relationship between mental health status and death anxiety among dental staff and students during the prevalence of COVID-19 pandemic. This suggests the impact of confounding factors in this area, which can be studied by future researchers and policy makers to design health promotion interventions.